RELATIONSHIP BETWEEN DEGREE OF OPTICAL NERVE DAMAGE ON LEVEL OF DEPRESSION AND ANXIETY PATIENT WITH PRIMARY GLAUCOMA: Oral Presentation - Observational Study - Resident - SETIAWAN, I KADEK AGUS; Rahayu, Ni Kompyang; Ariani, Ni Ketut Putri; Widiana, I Gde Raka; Kusumadjaja, I Made Agus; Juliari, I Gusti Ayu Made (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is one of the leading causes of irreversible global blindness and the second most commoncause of blindness in the world after cataracts. Depression and anxiety often occur in glaucomapatients when glaucoma is first diagnosed, the effect of decreased vision function in glaucoma, sideeffects of glaucoma therapy both medically and surgically and financial effects due to length oftreatment and loss of job due to limited vision. This study aims to determine the relationship of thedegree of optic nerve damage to the level of depression and anxiety in patients with primaryglaucoma. MethodsThis research is an analytic, prospective observational research with a cross-sectional studyapproach. The relationship between independent variables and dependent variables was analyzed. ResultsThe Man Whitney test found a significant difference in anxiety scores between the severe and mildto moderate groups with a p value of 0.020 . The ANCOVA test found that there was a relationshipbetween the degree of optic nerve damage in primary glaucoma and the level of anxiety aftercontrolling for control variables. ConclusionThis study can be concluded that there is a difference in the level of anxiety between the degree ofsevere and mild to moderate optic nerve damage. The level of anxiety itself corresponds to thedegree of damage to the optic nerve. The more severe the damage to the optic nerve, increased ofthe patient's anxiety score.